The Effect of Attitude, Motivation, and Self Efficacy on Entrepreneurial Interest of Generation Z in Bengkulu City - Tiara Elma Fira; Karona Cahya Susena; Suswati Nasution (Innovative Business Management Journal, 2026)
This study is motivated by the low level of entrepreneurial interest among Generation Z in Bengkulu City, despite the rapid growth of business opportunities in the digital era. This condition is assumed to be influenced by individual psychological factors,particularly attitudes toward entrepreneurship, entrepreneurial motivation, and self-efficacy. This research aims to analyze the effects of attitude, motivation, and self-efficacy on the entrepreneurial interest of Generation Z, both partially and simultaneously. The study employed a quantitative approach using a survey method by distributing questionnaires to 160 respondents selected through purposive sampling. The data were analyzed using validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²) with the assistance of SPSS version 23. The results indicate that attitude, motivation, and self-efficacy have a positive and significant effect on entrepreneurial interest. Attitude was found to be the most dominant variable compared to the others. The coefficient of determination value of 0.395 indicates that 39.5% of the variation in entrepreneurial interest can be explained by the three independent variables, while the remaining percentage is influenced by other factors outside the research model. These findings emphasize that strengthening positive attitudes, increasing motivation, and enhancing self-confidence are essential aspects in fostering entrepreneurial interest among Generation Z in Bengkulu City.